Strategy for environmental education and communications for the Caribbean - Rudder, Joy (Caribbean Conservation Association The GarrisonBB, 1995)
Outlines the background against which the Caribbean environmental consciousness has emerged and defines the areas in which important work in environmental education needs to progress rapidly. Provides a rationale for an implementation process which can heighten the effectiveness of the strategy through improved communications and a information systems network linking key sectors.